Pengaruh Penggunaan Media Pembelajaran Interaktif Berbasis CodeCombat terhadap Motivasi Belajar Siswa SMK Negeri 1 Panji pada Mata Pelajaran Informatika - Ahmad Ihsan; Arico Ayani Suparto; Firman Jaya (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effect of CodeCombat-based interactive learning media on students’ learning motivation in Informatics subjects at SMK Negeri 1 Panji. This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 72 students, divided into an experimental class of 36 students and a control class of 36 students. The experimental class was taught using CodeCombat, while the control class received conventional instruction. Data were collected using a 20-item Likert-scale learning motivation questionnaire that had been tested for validity and reliability. Data analysis was conducted using IBM SPSS through normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and N-Gain analysis. The results showed that the pretest scores of the experimental and control classes were not significantly different, with a significance value of 0.53 > 0.05. However, the posttest results showed a significant difference between the two classes, with p<0.001. The experimental class obtained a higher posttest mean score of 87.86 compared to the control class, which obtained 73.69. The N-Gain score of the experimental class was 0.6316, categorized as moderate or fairly effective, while the control class obtained 0.1867, categorized as low. These findings indicate that CodeCombat-based interactive learning media has a significant positive effect on improving students’ learning motivation in Informatics subjects.